OPTIMALISASI PENDAPATAN DAN LABA BANK UMUM SYARIAH MELALUI DANA PIHAK KETIGA DAN PENEMPATAN DANA - Rezatullah; Muhammad Nasir; Teuku Zulkarnain (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This study examines how third-party funds (DPK), placements with Bank Indonesia (PDBI), and placements with other banks (PDBL) affect income and profit of Islamic commercial banks in Indonesia, with income positioned as a mediating variable. The study uses a quantitative associative design and balanced panel data from 10 Islamic commercial banks during 2018–2022, producing 50 bank-year observations. Structural Equation Modeling (SEM) with AMOS was employed to estimate direct and indirect relationships at a 5% significance level. The results show that DPK and PDBI have significant negative effects on income, whereas PDBL has a significant positive effect. DPK does not directly affect profit, while PDBI has a significant negative effect and PDBL a significant positive effect. Income also has a significant effect on profit, although its coefficient is negative after the other funding-allocation variables are controlled. The mediation analysis indicates that income transmits the effects of DPK, PDBI, and PDBL to profit. These findings imply that increasing funding sources is insufficient without efficient allocation, liquidity management, and control of fund costs. Islamic banks should balance placements in liquid instruments with productive asset allocation to strengthen sustainable profitability.